Self-healing mechanisms in smart protective coatings: A review - Zhang, Fan; Ju, Pengfei; Pan, Mengqiu; Zhang, Dawei; Huang, Yao; Li, Guoliang; Li, Xiaogang (Corrosion science, 2018)
Self-healing coatings inspired by biological systems possess the ability to repair physical damage or recover functional performance with minimal or no intervention. This article provides a comprehensive and updated review on the advantages and limitations associated with common autonomous and non-autonomous self-healing mechanisms in protective organic coatings used for anti-corrosion purposes. The autonomous healing mechanisms are often enabled by embedding polymerizable healing agents or corrosion inhibitors in the coating matrices. For non-autonomous mechanisms, the healing effects are induced by external heat or light stimuli, which trigger the chemical reactions or physical transitions necessary for bond formation or molecular chain movement.